2011
DOI: 10.1016/j.virusres.2010.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Is HCMV a tumor promoter?

Abstract: Human cytomegalovirus (HCMV) is a beta-herpesvirus that causes persistent infection in humans and can cause severe disease in fetuses and immunocompromised individuals. Although HCMV is not currently causally implicated in human cancer, emerging evidence suggests that HCMV infection and expression may be specifically associated with human malignancies including malignant glioma, colon, and prostate cancer. In addition, multiple investigators have demonstrated that HCMV can dysregulate signaling pathways involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
159
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 149 publications
(187 reference statements)
0
159
1
7
Order By: Relevance
“…[7] The nucleic acids and proteins of HCMV have been found in many cancers such as colon, prostate, breast cancers, glioblastoma, medulloblasoma, mucoepidermoid carcinoma of the salivary glands and rhabdomyosarcoma. [8][9][10] One study showed that HCMV was detected by immunohistochemical analysis in the normal epithelial cells of the breast tissue and the malignant epithelial cells of breast carcinoma but it was higher in the later. [6] On the other hand, a recent study didn't find HCMV in breast cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The nucleic acids and proteins of HCMV have been found in many cancers such as colon, prostate, breast cancers, glioblastoma, medulloblasoma, mucoepidermoid carcinoma of the salivary glands and rhabdomyosarcoma. [8][9][10] One study showed that HCMV was detected by immunohistochemical analysis in the normal epithelial cells of the breast tissue and the malignant epithelial cells of breast carcinoma but it was higher in the later. [6] On the other hand, a recent study didn't find HCMV in breast cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…7 These findings imply that HCMV affects tumor progression, consistent with substantial evidence that HCMV has an oncomodulatory or even a direct oncogenic role in tumor development. [10][11][12][13][14] To determine whether treatment for HCMV improves the prognosis for GBM patients, we performed an exploratory clinical study, Valcyte Treatment of Glioblastoma Patients in Sweden (VIGAS), to assess the safety and potential efficacy of valganciclovir as an add-on therapy. 15 Forty-two patients with GBM were enrolled and received valganciclovir or placebo for 24 weeks in combination with temozolomide and/or radiation therapy.…”
mentioning
confidence: 99%
“…ЦМВ определяют в опухолях грудной и предстательной желез, толстого кишечника, медуллобластомах, глиобластомах и др. [1][2][3][4][5].…”
unclassified
“…Таким образом, ЦМВ имеет определенное избирательное более широкое распро-странение при нейроонкологических заболеваниях, тогда как другой родственный вирус -ВПГ в этой группе выявляют реже, чем при неврологических заболеваниях, и титр антител к ЦМВ меньше, чем при гинекологических заболеваниях. Сопоставление и анализ этих данных позволяют сделать заключение, что ЦМВ более распространен при нейроонкологических заболеваниях, что под-тверждают данные литературы о том, что ЦМВ кон-центрируются в очагах опухоли при глиобластоме и медуллобластоме [2][3][4][5][6]12]. Причина более частого инфицирования ЦМВ нейроонкологических больных неясна, а с объяснениями, что это может быть обус-ловлено угнетением иммунитета, трудно согласиться, поскольку титр антител к ЦМВ в крови этих пациентов в 3-4 раза выше, чем при других заболеваниях, т.е иммуносупрессии, как общей так и селективной, к этому вирусу нет.…”
unclassified
See 1 more Smart Citation